Chemotherapy combined with lenvatinib and PD-1 may be a potential better alternative option for advanced unresectable intrahepatic cholangiocarcinoma: a retrospective real-world study - Dong, Zhitao; Sui, Chengjun; Lu, Jiongjiong; Guo, Junwu; Duan, Kecai; Wang, Kui; Geng, Li; Dai, Binghua; Yang, Jiamei (Frontiers in Immunology, 2024)
Background Currently, the prognosis of advanced intrahepatic cholangiocarcinoma (ICC) is poor, and the current treatment methods are not effective. Objective The aim of this study was to evaluate the anticancer efficacy of chemotherapy combined with PD-1 inhibitors and tyrosine kinase inhibitors (TKIs) in patients with ICC. Methods We retrospectively screened patients with advanced intrahepatic cholangiocarcinoma (ICC) who received chemotherapy combined with lenvatinib and PD-1. We evaluated overall survival (OS), progression-free survival (PFS), the objective response rate (ORR), the disease control rate (DCR), the tumor shrinkage rate, and safety. Results We enrolled 95 patients with ICC and divided them into three groups with a median follow-up duration of 15.1 months. The chemotherapy group (chemo-regimen group), chemotherapy combined with immune checkpoint inhibitors (dual-regimen group), and chemotherapy combined with lenvatinib (triple-regimen group) had median OS times of 13.1 months, 20.8 months, and 39.6 months, respectively. Notably, the triple-regimen group had a significantly longer OS than did the chemo-regimen and dual-regimen groups. The chemo-regimen group, dual-regimen group, and triple-regimen group reported median PFS durations of 4.8 months, 11.9 months, and 23.4 months, respectively. Both combination groups exhibited significantly longer PFS than the chemotherapy-only group (P<0.05). The ORRs of the chemo-regimen, dual-regimen, and triple-regimen groups were 18.2%, 55.5%, and 54.7%, respectively. The DCRs were 72.7%, 90%, and 96.2%, respectively, indicating significantly better outcomes in the combination therapy groups. Conclusion The combination of chemotherapy with PD-1 inhibitors and lenvatinib demonstrates considerable efficacy and tolerability as a treatment strategy for patients with advanced ICC.